FROM THE HISTORY OF ANCIENT CERAMIC PRODUCTS DISCOVERED IN THE TERRITORY OF UZBEKISTAN - Isroiljon Urinbayev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The history of the brick wards related to the Zoroastrian religion is examined in this article. Features, forms, and decorations of the artifacts found at archaeological excavations in the different regions of Uzbekistan, are studied in him. The focus is on the history of the Ostodons, which reflects the customs and rituals of historical periods, such as mourning events. The history of the ceramics found in the monuments is analyzed, the processes of restoration and repair are studied, scientific research works are classified and studied.